The Influence Of Religiosity And Organizational Commitment On Organizational Citizenship Behaviours: A Review Of Literature - Olowookere, Elizabeth Ibukunoluwa (Advances in Social Sciences Research Journal, 2014)
In an attempt to cultivate and promote organizational citizenship behaviours, many scholars have identified its antecedents to include organizational characteristics (e.g. working conditions, organizational policies and procedures, leadership style and work environment), employee characteristics (e.g. personal attributes, beliefs, attitude and dispositions) and work characteristics (e.g. job content and design). This paper reviewed literature on religiosity and organizational commitment as antecedents of OCB. Further, it accentuated the connection among these variables (religiosity, organizational commitment and organizational citizenship behaviours). It was observed that religiosity and organizational commitment are important variables that have been linked with organizational citizenship behaviours. Religiosity was associated with enhanced team work, greater kindness, fairness, honesty, trust, concern for others and OCB. Similarly, most studies claimed that organizational commitment enhances the performance of OCB. However, organizational commitment and OCB are very similar constructs, with one viewed as the behavioural demonstration of the other. This paper concluded that organizational commitment and OCB share similar antecedents such that any construct or variable related to one is automatically related to the other. Therefore, religiosity can serve as an antecedent of both organizational commitment and OCB. Finally, since most of the reviewed literatures are foreign, it was recommended that an empirical research be conducted to further validate these claims especially in the Nigerian work context. Keywords: Religiosity, Organizational Commitment, Organizational Citizenship Behaviours